Dietary Phosphorus Reduced Hepatic Lipid Deposition by Activating Ampk Pathway and Beclin1 Phosphorylation Levels to Activate Lipophagy in Tilapia Oreochromis niloticus - Liu, Xiangyuan; Zhao, Tao; Wei, Xiaolei; Zhang, Dianguang; Lv, Wuhong; Luo, Zhi (Frontiers in Nutrition, 2022)
High-phosphorus diet (HPD) reduces lipid deposition and significantly influences lipid metabolism. However, the relevant mechanism is unknown. Herein, using widely-cultured teleost tilapia Oreochromis niloticus as the experimental animals, we found that HPD and Pi incubation reduced triglyceride (TG) content (P≤0.05), suppressed lipogenesis, activated AMP-activated protein kinase (AMPK) pathway and autophagy (P≤0.05), and increased fatty acid β-oxidation and lipolysis in tilapia liver and hepatocytes (P≤0.05). Our further investigation indicated that Pi treatments activated the lipophagy and facilitated mitochondrial fatty acid β-oxidation, and according reduced TG deposition (P≤0.05). Mechanistically, phosphorus increased the AMPKα1 phosphorylation level at S496 and Beclin1 phosphorylation at S90, and Beclin1 phosphorylation by AMPKα1 was required for phosphorus-induced lipophagy and lipolysis. Our study revealed a mechanism for Beclin1 regulation and autophagy induction in response to high-phosphorus diet, and provided novel evidences for the link between dietary phosphorus addition and lipolytic metabolism via the AMPK/Beclin1 pathway. Our results also suggested that AMPK should be the potential target for the prevention and control of lipid metabolic disorders. Overall, these results suggested that HPD reduced hepatic lipid deposition by activating AMPK pathway and Beclin1 phosphorylation levels to activate lipophagy, which provided potential targets for the prevention and control of fatty liver in fish.